Organic tracers of primary biological aerosol particles at subtropical Okinawa Island in the western North Pacific Rim. Issue 11 (2nd June 2015) - Zhu, Chunmao; Kawamura, Kimitaka; Kunwar, Bhagawati
Abstract: Primary biological aerosol particles (PBAPs) play an important role in affecting atmospheric physical and chemical properties. Aerosol samples were collected at Cape Hedo, Okinawa Island, Japan, from October 2009 to February 2012 and analyzed for five primary saccharides and four sugar alcohols as PBAP tracers. We detected high levels of sucrose in spring when blossoming of plants happens and prolifically emits pollen to the air. Concentrations of glucose, fructose, and trehalose showed levels higher than the other saccharides in spring in 2010. In comparison, primary saccharide levels were mutually comparable in spring, summer, and autumn in 2011, indicating the interannual variability of their local production in subtropical forests, which is driven by local temperature and radiation. High trehalose events were found to be associated with Asian dust outflows, indicating that Asian dust also contributes to PBAPs at Okinawa. Sugar alcohols peaked in summer and correlated with local precipitation and temperature, indicating high microbial activities. Positive matrix factorization analysis confirmed that the PBAPs are mainly derived from local vegetation, pollen, and fungal spores. A higher contribution of PBAP tracers to water‐soluble organic carbon (WSOC) was found in summer (14.9%). The annual mean ambient loadings of fungal spores and PBAPs were estimated as 0.49 µg m −3 and 4.12 µg m −3, respectively, using the tracer method. We report, for the first time, year‐round biomarkers of PBAP and soil dust and their contributions to WSOC in the subtropical outflow region of the Asian continent. Key Points: PBAPs in Okinawa aerosols are largely affected by sources from local forest PBAP emissions from forest contribute largely to WSOC in aerosols Ambient fungal spore and PBAP loadings at Okinawa are estimated